2012
DOI: 10.5694/mja11.11468
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and measurement of albuminuria or proteinuria: a position statement

Abstract: Summary Optimal detection and subsequent risk stratification of people with chronic kidney disease (CKD) requires simultaneous consideration of both kidney function (glomerular filtration rate [GFR]) and kidney damage (as indicated by albuminuria or proteinuria). Measurement of urinary albuminuria and proteinuria is hindered by a lack of standardisation regarding requesting, sample collection, reporting and interpretation of tests. A multidisciplinary working group was convened with the goal of developing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(94 citation statements)
references
References 51 publications
4
88
1
1
Order By: Relevance
“…Currently, universal thresholds are used almost exclusively, while several prior studies and strategies suggested gender-specific cut-off points to define pathological UAE. It has also been suggested that albuminuria may be less important in women, primarily due to lower muscle mass and urinary creatinine excretion with potential overestimation of ACR [12,13,30,31,32]. Our findings partly contradict these views and rather strengthen the foundations of newer guidelines, such as KDIGO [15], using universal ACR thresholds for CKD diagnosis and classification and thereby simplifying daily clinical practice.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Currently, universal thresholds are used almost exclusively, while several prior studies and strategies suggested gender-specific cut-off points to define pathological UAE. It has also been suggested that albuminuria may be less important in women, primarily due to lower muscle mass and urinary creatinine excretion with potential overestimation of ACR [12,13,30,31,32]. Our findings partly contradict these views and rather strengthen the foundations of newer guidelines, such as KDIGO [15], using universal ACR thresholds for CKD diagnosis and classification and thereby simplifying daily clinical practice.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, day-to-day variability in urinary albumin excretion (UAE) can be substantial (25-50%), reflecting both biological variability and changes in disease status [9,10]. Urinary creatinine excretion is also lower in women [11]; therefore, some previous guidelines suggest different albumin-creatinine ratio (ACR) cut-off values for diabetic men and women [12,13,14]. The scientific basis for using gender-specific cut-offs, particularly for non-diabetic individuals, has been weak, and most guidelines, including the 2012 KDIGO guidelines on Chronic Kidney Disease (CKD) diagnosis and classification, therefore use universal thresholds [15].…”
Section: Introductionmentioning
confidence: 99%
“…(18) This method of classifying albuminuria reduces costs and allows for easier comparison in future studies. Johnson et al (13) likewise recommended that if the initial urine ACR test was negative, repeat testing was not required until the next recommended testing interval. However, the criteria for diagnosis of albuminuria in the current study did not strictly adhere to the Kidney Disease Outcomes Quality Initiative Clinical Practice Guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…(12) The proteincreatinine ratio (PCR) test may be used in place of the ACR test if ACR is more than 30 mg/mmoL; this is because the relationship between ACR and PCR is non-linear, and higher ACRs could not adequately predict the amount of 24-hour urinary protein. (13) Since the switch from the micral test to the quantitative urine ACR test for diagnosis of microalbuminuria, all doctors working in the polyclinic had been briefed and reminded to offer a second urine test if the first urine sample showed ACR > 2.5 mg/mmoL for male patients and > 3.5 mg/mmoL for female patients.…”
Section: Methodsmentioning
confidence: 99%
“…Recent guidelines recommend measuring albuminuria in all CKD patients based on the prognostic importance of albuminuria for kidney disease outcomes, as well as for cardiovascular disease and mortality [5][6][7]. Although 24-h urine albuminuria is the gold standard for quantitative measurement, the preferred method for assessing albuminuria in both diabetic and non-diabetic patients is urine albumin-to-creatinine ratio (ACR) measurement in a first-void spot urine specimen [8,9]. Considering the cost required for immunoassays of albuminuria, however, whether testing for both albuminuria and proteinuria is necessary among CKD patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%